Theory of relaxation parameters of the spectrum shape in the impact approximation-II: Simplifications, application for qQ(J,K) doublets in the v1 band of NH3 self-broadening; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 141 - Cherkasov M. R. Mikhail Romanovich (2014, 2014)
Title screen